2020
DOI: 10.1016/j.eclinm.2020.100447
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean delivery rates and analgesia effectiveness following injections of sterile water for back pain in labour: A multicentre, randomised placebo controlled trial

Abstract: Background About a third of women experience severe back pain during labour. Injecting small volumes of intracutaneous sterile water into the lumbar region can be used to relieve this pain, however the procedure is controversial and previous reviews call for high quality trials to establish efficacy. We evaluated the impact on birth outcomes and analgesic effects of sterile water injections. Methods A multicentre, double-blind trial undertaken between December 2012 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 33 publications
(56 reference statements)
2
19
0
11
Order By: Relevance
“…A recent placebo-controlled trial demonstrated the efficacy of sterile water injections into the lumbar region to relieve back pain in labour with no detrimental side effects [15]. Back pain in labour is different and may occur independently from abdominal labour pain [16].…”
Section: Background {6a}mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent placebo-controlled trial demonstrated the efficacy of sterile water injections into the lumbar region to relieve back pain in labour with no detrimental side effects [15]. Back pain in labour is different and may occur independently from abdominal labour pain [16].…”
Section: Background {6a}mentioning
confidence: 99%
“…Back pain in labour is different and may occur independently from abdominal labour pain [16]. Furthermore, the injections given into the lumbar region for back pain have no effect on abdominal contraction pain [15,17]. Injections of sterile water are acutely painful for a brief period, and this is known to act as a deterrent to both women and clinicians [18,19].…”
Section: Background {6a}mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that SWI has been proven to be a highly effective pain relief method, without any adverse side effects [ 4 , 7 ], some women are doubtful of the method. Earlier it has been reported that some women rated the injection pain as more painful than the contraction pain [ 10 ] with a self-reported VAS of 90–100 mm [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along with several smaller studies, a large double-blind, randomized controlled trial successfully demonstrated that SWI could provide effectively relief for low back pain during childbirth [ 7 ]. Clinical guidelines for the use of the procedure have earlier been published [ 4 ].…”
Section: Introductionmentioning
confidence: 99%